2013
DOI: 10.1097/brs.0b013e3182793e51
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Loosening of Pedicle Screw As a Result of Metal Wear Debris in a Pediatric Patient

Abstract: Metal wear debris can form in pediatric patients during the healing process after spinal fusions or when pseudarthrosis is present. Clinically, this manifests as back pain with a possible aseptic inflammatory abscess. Hardware removal can achieve resolution of symptoms and regression of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…Stress shielding, decreasing the load transferred through the bony tissue, resulting in remodeling of the bone surrounding the screw, was reported as another major reason for screw loosening . Additionally, the presence of wear debris was reported to induce osteolysis and consequent screw loosening . Of the mechanisms, microfracture and bone resorption triggered by excessive stress of the surrounding bone are the most common.…”
mentioning
confidence: 99%
“…Stress shielding, decreasing the load transferred through the bony tissue, resulting in remodeling of the bone surrounding the screw, was reported as another major reason for screw loosening . Additionally, the presence of wear debris was reported to induce osteolysis and consequent screw loosening . Of the mechanisms, microfracture and bone resorption triggered by excessive stress of the surrounding bone are the most common.…”
mentioning
confidence: 99%
“…Richman et al [9] recently reported a case of a 19-year-old male who presented with sudden onset of a neurologic deficit and pain 4 years after posterior spinal fusion for adolescent idiopathic scoliosis. A review of several cases of spinal metallosis after spinal fusion showed that most incidents involved invasion of the spinal canal leading to neural compression (except for one case reported by Botulin et al [10] as persistent back pain).…”
Section: Discussionmentioning
confidence: 99%
“…Late neurological complications, occurring years after successful spinal instrumentation, have rarely been reported in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Although some authors suggest that neurological symptoms appear due to the formation of epidural metallosis adjoining the hook-rod construct, the cause of the new-onset pain in our cases was related to direct compression of the canal by dislodged laminar hooks in the thoracolumbar region [1,11].…”
Section: Introductionmentioning
confidence: 86%